Assessment of pain in others - searching for what matters - Modić Stanke, Koraljka (Array, 2009)
Misjudgments of pain in others have many unpleasant consequences and should be avoided or at least minimized. Therefore we have to understand the basis of these misjudgments, which requires exploring factors involved in assessment of pain in others. The aim of this study was to investigate whether assessment of other people’ s experience of pain is mediated by the observer’ s empathy, and to determine whether it is affected by the observer’ s experience with experimentally induced pain. Observers (94 female and 32 male participants) watched 6 video-tapes (3 volunteers in 2 different experimentally induced painful situations) and rated pain intensity and unpleasantness experienced by the person on the tape. Observers’ empathy was measured as trait and state, and their experience was manipulated by participation in one experimentally induced painful situation. Female participants were divided in 3 groups: no experience, last year’ s experience and present experience, while male participants were only in no experience situation. Results confirmed that observers generally underestimate pain in others, the mistake being larger when person on tape reported higher pain intensity. Empathy was not correlated with judgment of pain in others, but experience had some effect - observers who had experience with experimentally induced pain gave more accurate ratings of other people’ s pain experience. Results suggest that personal experience, but not empathy, plays a certain role in assessment of pain in others.